Опыт корпоративного обследования электрических цепей 110 кВ Сибири: монография - Боровиков В. С. Вячеслав Сергеевич; Волков М. В. Михаил Валерьевич; Иванов В. В. Виталий Валерьевич; Литвак В. В. Валерий Владимирович; Мельников В. А. Василий Александрович; Погонин А. В. Андрей Владимирович; Харлов Н. Н. Николай Николаевич (Томск, Изд-во ТПУ, 2010)
Заглавие с титульного экрана